The Goblin Spider Genus Aprusia Simon, 1893 (Araneae: Oonopidae) - Grismado, Cristian José (2011)
The south Asian goblin spider genus Aprusia Simon (Araneae: Oonopidae) consists of five species and is found in southwestern India and Sri Lanka. Although the type species A. strenuus Simon is known only from two juvenile syntypes, new topotypical material from Sri Lanka allowed a redefinition of the genus and species. Ischnothyreus vestigator Simon, also from Sri Lanka, is transferred to Aprusia based on recently collected topotypical specimens. The female is described for the first time. Three new species are described: A. veddah Grismado and Deeleman, A. kataragama Grismado and Deeleman (both from Sri Lanka), and A. kerala Grismado and Deeleman (from southwestern India). The genus is recognized by the relatively small to medium-sized dorsal scutum on the abdomen of both sexes, the strong macrosetae on the forelegs and by the conformation of the male palp, with the cymbium and bulb fused and a tiny, slightly sclerotized embolus.